Pengembangan SSP biologi domain kreativitas untuk meningkatkan karakter kreatif, tanggung jawab dan prestasi belajar siswa - Ary Kusmawati (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2017)
Tujuan penelitian ini untuk: (1) mengembangkan SSP Biologi berbasis domain kreativitas dalam mengembangkan karakter kreatif dan tanggung jawab pada diri siswa; (2) mengetahui kualitas SSP Biologi berbasis domain kreativitas untuk meningkatkan karakter kreatif dan tanggung jawab pada siswa; (3) mengetahui SSP Biologi berbasis domain kreativitas yang dihasilkan mampu meningkatkan karakter kreatif dan tanggung jawab serta prestasi hasil belajar siswa. Metode yang digunakan dalam penelitian ini adalah Research and Development (R D). Subjek uji coba dalam penelitian ini adalah kelas XI IPA 3 (sebagai kelas kontrol) dan XI IPA 5 (sebagai kelas treatmen) yang masing-masing kelas terdiri atas 30 siswa. Pengumpulan data dilakukan dengan menggunakan pedoman wawancara, lembar validasi SSP, angket, lembar observasi, dan tes yang terdiri atas pretest dan posttest. Hasil penelitian dalam pengembangan perangkat SSP Biologi domain kreativitas untuk meningkatkan karakter kreatif dan tanggung jawab pada siswa yang terdiri atas pengembangan Silabus, RPP, Materi ajar, LKS, penilaian tes belajar siswa sudah valid dan layak digunakan karena memiliki kategori sangat baik. Perangkat SSP Biologi domain kreativitas untuk meningkatkan karakter kreatif dan tanggung jawab mampu meningkatkan karakter kreatif dan tanggung jawab pada siswa dengan katagori sangat baik.Kata Kunci: SSP, kreativitas, karakter, kreatif, tanggung jawab Developing Creativity Domain Biology SSP to Improve Students' Creative Character, Responsibility, and Learning Achievement AbstractThis study aims to: (1) develop creativity-domain-based biology SSP to improve the creative and responsibility character in students. (2) reveal the quality the creativity-domain-based biology SSP to improve the creativity and responsibility characters of students.(3) knowing quality developing the creativity-domain-based biology SSP to improve the creativity, responsibility character and the resulting study of student. The method in this study was Research and Development (R D) consisting of 10 primary steps developed by Borg Gall; this study, however, used only steps 1 to 7, i.e.a preliminary study, planning, SSP draft construction and validation, a small-scale try out, evaluation and revision, a large-scale try out, and evaluation and final revision. The try out subjects were grade XI IPA students, consisting of 15 Grade XI IPA 1 students for the small-scale tryout and 30 Grade XI IPA 3 students as the control class, 30 Grade student of XI IPA 5 as the experimental class. The data were collected by means of an interview guide, a kit validation sheet, a questionnaire, an observation sheet, and tests consisting of a pre-test and post-test. Feedback and suggestion for the developed SSP in the small-scale try out stage were used as the basis for the SSP revision in the subsequent tryout. The result of study consisting of the development of syllabus, lesson plant, teaching materials, worksheets, student assessment test, according to the research is valid and fit for use because it is in a very good category. The SSP device creativity-domain-based biology to enhance the creativity and responsibility characters can improve creativity and responsibility characters of the students, which is a very good character.Keywords: SSP, creativity, character, creative, responsibility